Characteristics of women presenting with abortion at the Komfo Anokye Teaching Hospital, Kumasi, Ghana - Agyei, Helena (2014)
A thesis submitted to the Department Of Community Health in partial fulfilment of the requirements for the degree of Master of Public Health (MPH) In Health Services Planning and Management, August - 2012